2018
DOI: 10.21608/ebwhj.2018.7511
|View full text |Cite
|
Sign up to set email alerts
|

Calcium infusion plus or minus cabergoline for prevention of ovarian hyperstimulation syndrome: Randomized double-blind placebo-controlled trial

Abstract: Aim: To evaluate the interaction of adding oral cabergoline (OC) to calcium infusion as a preventive modality for ovarian hyperstimulation syndrome (OHSS) in risky women undergoing controlled ovarian hyperstimulation (COH) in context of in-vitro fertilization (IVF) / intracytoplasmic sperm injection (ICSI). Patients and Methods: This prospective, double-blind, randomized, placebo-controlled trial was conducted at Benha IVF center of Obstetrics and Gynecology Department of Benha University and Nour Al Hayah Fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The extended GnRH agonist regimen was used to stimulate 180 individuals who were at high risk of having OHSS and were randomly assigned in a ratio of one to one to the cabergoline group and the calcium gluconate group, and it was discovered that calcium gluconate was more advantageous for preventing OHSS. There are other articles comparing calcium gluconate, cabergoline, and other medications for preventing OHSS [ 14 ], but based on our research, none of them demonstrated the combined effect of calcium gluconate and cabergoline, with the exception of one article that contrasted the combined effects of these two with calcium gluconate infusion alone and found that the combined effect was beneficial [ 15 ]. We made the decision to administer the patient a cabergoline tablet and a calcium gluconate (10%) intravenous infusion together (starting on the day of OPU, for three days) since OHSS is more severe in PCOS women receiving IVF/ICSI treatment because of increased arterial permeability, which causes proteinaceous fluid to flow into third spaces [ 16 ].…”
Section: Discussionmentioning
confidence: 93%
“…The extended GnRH agonist regimen was used to stimulate 180 individuals who were at high risk of having OHSS and were randomly assigned in a ratio of one to one to the cabergoline group and the calcium gluconate group, and it was discovered that calcium gluconate was more advantageous for preventing OHSS. There are other articles comparing calcium gluconate, cabergoline, and other medications for preventing OHSS [ 14 ], but based on our research, none of them demonstrated the combined effect of calcium gluconate and cabergoline, with the exception of one article that contrasted the combined effects of these two with calcium gluconate infusion alone and found that the combined effect was beneficial [ 15 ]. We made the decision to administer the patient a cabergoline tablet and a calcium gluconate (10%) intravenous infusion together (starting on the day of OPU, for three days) since OHSS is more severe in PCOS women receiving IVF/ICSI treatment because of increased arterial permeability, which causes proteinaceous fluid to flow into third spaces [ 16 ].…”
Section: Discussionmentioning
confidence: 93%